CHLORARGYRITE AND ACANTHITE IN PM-10 PARTICLES IN TIKVES AREA (Natural Resources and Technology, 2017)
The investigations performed by applying electron microscopy (SEM-EDS technique) unequivocallyconfirmed the results made by using XRF, the X-ray diffraction and the results from the determination of chemicalcomposition of particles PM-10 with the application of the ICP-AES and ICP-MS. From the results performed withall of the applied techniques it can be concluded that the presence of specified mineral phases that have typicallyanthropogenic origin are registered as well as the mineral phases that have lithogenic origin or the origin of thepresent geological structure. Therefore, it can be concluded that the urban dust with a sizes below 10 μm (PM-10) inthe Tikveš area originated from lithogenic and anthropogenic processes. It can be concluded that the phasecomposition of the particles PM10 from Tikveš area consisting of mineral phases which have anthropogenic originconfirmed by the high content of Fe, Ni, Cu, Zn, Ag, Cr (present in higher content in the ore processed in theferronickel smelter), and by the presence of the minerals like: chlorite, amphibole, pyroxene, magnetite, chromites,Ag-minerals (chlorargyrite), metallic forms of Mn-Cr, Cu-Zn (also present in the ore processed in the smelter plant).The lithogeneic origin of the part of PM10 is confirmed by the presence of minerals quartz, calcite or plagioclaseclay minerals.